2015
DOI: 10.3390/e17020539
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Direct Fuel Injection Strategies on Cycle-by-Cycle Variability in a Gasoline Homogeneous Charge Compression Ignition Engine: Sample Entropy Analysis

Abstract: Abstract:In this study we summarize and analyze experimental observations of cyclic variability in homogeneous charge compression ignition (HCCI) combustion in a single-cylinder gasoline engine. The engine was configured with negative valve overlap (NVO) to trap residual gases from prior cycles and thus enable auto-ignition in successive cycles. Correlations were developed between different fuel injection strategies and cycle average combustion and work output profiles. Hypothesized physical mechanisms based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Early NVO injection was applied at a start of injection (SOI) timing of À40 CA. Earlier studies showed that to a high extent exhaustfuel reactions happen at this injection timing [8]. As a result, high concentrations of pyrolysis products were observed in combustible mixture.…”
Section: Experimental Conditions and Proceduresmentioning
confidence: 97%
“…Early NVO injection was applied at a start of injection (SOI) timing of À40 CA. Earlier studies showed that to a high extent exhaustfuel reactions happen at this injection timing [8]. As a result, high concentrations of pyrolysis products were observed in combustible mixture.…”
Section: Experimental Conditions and Proceduresmentioning
confidence: 97%
“…The numerical procedure of entropy estimation (from experiments and mathematical models), in the forms presented above, have been applied to physical phenomena in the field of physiology [ 19 , 20 , 21 , 22 , 23 ], medicine [ 27 , 30 ], mechanics [ 13 , 14 , 16 , 18 ], and thermodynamics [ 15 ], etc. In the present paper, the CMSE is applied to signals of a pendulum system with a friction effect.…”
Section: Multiscaled Entropymentioning
confidence: 99%
“…In this paper, we discuss the concept of multi-scaled entropy applied to response time series of dynamical systems in the case of a pendulum with a frictional load (previous related studies on mechanical systems include [ 13 , 14 , 15 , 16 ]). In the following sections, we define the mathematical model, introduce the entropy approach and discuss simulation results.…”
Section: Introductionmentioning
confidence: 99%
“…It serves to reduce soot, Carbon Oxides (CO), and Nitrogen Oxides (NO x ) simultaneously. This option is commercially presented in three different approaches: 1/Homogeneous Charge Compression Ignition (HCCI) [5][6][7], which provides the ignition of a lean homogeneous air-fuel mixture; 2/Premixed Charge Compression Ignition (PCCI), is an adaptative form of HCCI, it controls combustion instability by a second injection to enrich wherever flame should be started; 3/Reactivity Controlled Compression Ignition (RCCI) [7,8], based on high reactivity fuel, that is, diesel and nheptane as well as a low reactive fuel such as gasoline, iso-octane, and natural gas. The LTC is based on a combination of injection timing, mixture homogeneity, and dual fuel mode.…”
Section: Introductionmentioning
confidence: 99%